A new species of Pseudopaludicola Miranda-Ribeiro, 1926 (Anura: Leiuperidae) from the state of Mato Grosso, Brazil, with comments on the geographic distribution of Pseudopaludicola canga Giaretta & Kokubum, 2003. - Pansonato, Andre; Morais, Drausio H.; Avila, Robson W.; Kawashita-Ribeiro, Ricardo A.; Strussmann, Christine; Martins, Itamar A. (My University, 2012)
A new species of Pseudopaludicola is described from the state of Mato Grosso, western Brazil. The new species inhabits the transition zone between Brazilian Cerrado and Amazon rainforest in northern Mato Grosso, and is characterized by its medium size (snout-vent length 12-17 mm), lack of T-shaped terminal phalanges, toe tips not expanded laterally, presence of two antebrachial tubercles, and smooth upper eyelids. The advertisement call of the new species consists of a series composed of 11-74 non-pulsed notes. Mean dominant frequency is 3938 Hz. Each note presents a slight ascendant frequency modulation in its first half, and another ascendant modulation in its last half. We also present new data on the distribution and conservation status of Pseudopaludicola canga.